Gruppenaufnahme
Oben von links: Häcker, Josef; Brunner, Heinrich; Helfrich, Mathias; Aulbach, Michael, Syndikus, Max; Kullmann, Josef; Mantel, Johannes; Kullmann, Ludwig; Herold, Johannes; Herold, Albert; Büttner, Vinz.; Schnatz, Georg; Hugo, Alfons; Heßler, Nick.;Arnold, Joh.; Büttner, Joh.; Staudt, Franz; Schneider, Rudolf; Sauer, Georg; Staudt, Franz; Hesele, Alois; sitzend unten: Maier, Vinz.; Schnatz, Alb.; Heßler, Georg; Zahn, Ludwig; Kolb, Jos.; Aßmann, Edm.; die beiden Kinder: links Büttner, Adam;rechts Zahn, Hans; Bemerkungen: Reproduktion